Pengembangan Media E-Book Untuk Meningkatkan Hasil Belajar Siswa Mata Pelajaran Pendidikan Pancasila - Eriyansari, Manda; Bektiningsih, Kurniana (Paedagogie, 2026)
This development research aims to produce a valid, feasible, and effective e-book media to improve the learning outcomes of phase B students in Pancasila Education, specifically the meaning and application of the Pancasila principles. Using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model at SDN Sekaran 01 from November 2025 to January 2026, the media assessment results were validated by media experts (score 95%, very feasible) and material experts (93%, very feasible). A large group trial showed a significant increase in learning outcomes (paired t-test sig. 0.001; N-Gain 0.68 moderate), with positive responses from teachers (92%) and students (90%), indicating that this media effectively supports interactive and contextual learning.